2015
DOI: 10.1590/1982-021620153314
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre o tempo de magistério e a autoavaliação vocal em professores universitários: estudo observacional transversal

Abstract: OBJETIVO: verificar a associação entre o tempo de magistério e a autoavaliação vocal em professores universitários. MÉTODOS: participaram deste estudo 42 professores universitários, os quais responderam a um questionário para caracterização da amostra e identificação das sensações/sintomas vocais e ao Protocolo do Perfil e Participação e Atividades Vocais RESULTADOS: os participantes foram considerados jovens quanto ao tempo de magistério, pois a mediana foi de 8,5 anos, sendo que os autores não limitaram um n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
(21 reference statements)
3
11
0
6
Order By: Relevance
“…The major frequency of dry throat in the period which the teacher did not use the dynamic soundfield system corroborates to other studies showing the dry throat symptom is the most reported symptom by Brazilian teachers in recent researches 22,23 , which relate the unfavorable work conditions, as background noise, the acoustic improper set of classroom, strain while talking, vocal misuse, and lack of hydration 22 . Furthermore, other studies show direct relation between the increase in mean loudness and the noise in classroom 3,7 .…”
Section: Discussionsupporting
confidence: 87%
“…The major frequency of dry throat in the period which the teacher did not use the dynamic soundfield system corroborates to other studies showing the dry throat symptom is the most reported symptom by Brazilian teachers in recent researches 22,23 , which relate the unfavorable work conditions, as background noise, the acoustic improper set of classroom, strain while talking, vocal misuse, and lack of hydration 22 . Furthermore, other studies show direct relation between the increase in mean loudness and the noise in classroom 3,7 .…”
Section: Discussionsupporting
confidence: 87%
“…One of the biggest interests on voice researches is the teacher's vocal health, interest that keeps rising since the last decade [1][2][3][4][5][6][7][8][9][10][11][12] as a result of the importance of the craft the teacher exert before the society 8 . Since 1997, the Speech Federal Council understands that most voice disturbs must be classified as "occupational diseases" 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Para os fatores 1, 2 e 3 foram encontrados escores médios de 5,16, 1,44 e 5,8 respectivamente para indivíduos saudáveis e 24,47, 6,9 e 7,71 respectivamente para indivíduos com no grupo "falha", ou seja, 67,4%. Contudo, tal fato aparenta não significar que as queixas e sintomas vocais de professores refletem na limitação de suas atividades laborais e extralaborais 23 .…”
Section: Discussionunclassified
“…Em comparação com os gêneros masculino e feminino em todos os professores, o sintoma mais comum para os homens foi ardência na garganta, enquanto que, para as professoras, foi o cansaço ao falar, assim como os sintomas rouquidão e ardência na garganta, corroborando com estudos nacionais 23,24 . Além disso, mulheres estão mais propensas a obter escores de protocolos vocais próximos a indivíduos com disfonia 3 .…”
Section: Discussionunclassified